2004
DOI: 10.1029/2004jd005186
|View full text |Cite
|
Sign up to set email alerts
|

Stratosphere‐troposphere exchange of mass and ozone

Abstract: [1] This study examines the relationship between the extratropical cross-tropopause fluxes of mass and ozone. The adiabatic and diabatic components of the net fluxes are also compared. The rate of change of mass in the lowermost stratosphere and the flux across the 380 K isentropic surface are used to determine the net tropopause mass flux in the framework of a global circulation model. The diabatic mass flux is calculated from the heating rate at the tropopause, and the adiabatic component is determined by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
113
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(145 citation statements)
references
References 53 publications
30
113
1
1
Order By: Relevance
“…This is important for this study because the magnitude and seasonal cycle of STE is strongly tied to the Brewer-Dobson circulation through the overworld wave driving (Holton et al, 1995). Olsen et al (2004) showed that the exchange of mass and ozone between the stratosphere and troposphere in a CTM simulation driven with the GEOS-4 GCM meteorological fields compares well with estimates derived from observations. In comparison, a CTM simulation using an older version of the GEOS-4 Data Assimilation System (GEOS-4 DAS) produces a "fast" Brewer-Dobson circulation and "young" age of air as compared to the observations .…”
Section: The Global Modeling Initiative Combinedsupporting
confidence: 58%
See 1 more Smart Citation
“…This is important for this study because the magnitude and seasonal cycle of STE is strongly tied to the Brewer-Dobson circulation through the overworld wave driving (Holton et al, 1995). Olsen et al (2004) showed that the exchange of mass and ozone between the stratosphere and troposphere in a CTM simulation driven with the GEOS-4 GCM meteorological fields compares well with estimates derived from observations. In comparison, a CTM simulation using an older version of the GEOS-4 Data Assimilation System (GEOS-4 DAS) produces a "fast" Brewer-Dobson circulation and "young" age of air as compared to the observations .…”
Section: The Global Modeling Initiative Combinedsupporting
confidence: 58%
“…The flux of a trace gas across the tropopause is determined by the convolution of air mass flux and its concentration in the LS (Olsen et al, 2004). The comparison between DT fix , with constant mixing ratio above the tropopause, and DT 6−month , with a specified annual cycle above the tropopause, segregates the contribution from seasonal changes in mass flux (Fig.…”
Section: Stt: Timescale and Mechanismmentioning
confidence: 99%
“…This feature was observed on all three flights during spring and thus seems not to be an individual outlier. Furthermore, in the time from April to July stratospheric mass transport into the upper and mid-troposphere is known to occur regularly (Appenzeller and Holten, 1996;Allen et al, 2003;Zanis et al, 2003;Olsen et al, 2004;Schoeberl, 2004). Moreover, Sprenger et al (2003) and Sprenger and Wernli (2003) demonstrated that cross-tropopause mass flux is highest in the midlatitudes where these mercury profiles were measured.…”
Section: North Americamentioning
confidence: 92%
“…winter. This feature is followed by approximately 100 days of transport until reaching the tropopause (Olsen et al, 2004 Olsen et al (2013, Fig. 5), where observations of O 3 mixing ratio in the stratosphere (θ = 380 K) from Microwave Limb Sounder (MLS) are combined with MERRA reanalysis meteorological fields.…”
Section: Horizontal Distributions Of O 3 and Comentioning
confidence: 99%